Molecular Detection of Some Virulence Genes of Salmonella Typhymurium and Salmonella Enteritidis Isolated from Patients Suffering Watery Diarrhea - Lamees A. Abdul-Lateef (Journal of Global Pharma Technology, 2016)
Salmonella enterica virulence factors can be divided into chromosomal, plasmid and bacteriophages encoded virulence factors. Many of the Salmonella virulence factors, such as adhesion, invasion, and toxin genes are clustered in certain areas of the chromosome known as “Salmonella pathogenicity islands” (SPI). A total of 200 clinical stool samples were collected during this study which obtained from patient Suffering from watery diarrhea who a dmintted to three main hospitals of Babylon Governorate: Merjan Medical city, Al-Hillah Surgical Teaching Hospital and Babil Teaching Hospital for Women and Children during a period of three months (from july 2018 to September 2018). Out of 200 specimens 35(17.5%) were detected by culture and vitek2 compact, 24 (12%) of them were confirmed by PCR using target gene, (17) Salmonella typhimurium and (7) Salmonella enteritidis. PCR was conducted to determine the some virulence genes of the isolates by using primers inv A, sdiA and sifA. The PCR amplification products were visualized by electrophoresis on 1% agarose gels for 35min at 70v. The sizes of the amplicons were determined by comparison to the 200 bp allelic ladder. Among isolates studies it was found that invA gene present in 13(54)% isolates of S. enterica ,(9) isolates of S. typhimurium and (4) isolates of S. enteritidis , sdiA gene it was found in all isolates (100)% while sifA gene it was found in all isolates only isolate number 18 not contained this gene 23(96)%.Keywords: Salmonella typhimurium, S. enteritidis, invA, sdiA and sifA.